Optimasi Kinerja Analitik Terhadap Penentuan Kadar Fluorin Pada Batubara Dengan Metode Spektrofotometer Visible - Adha, Laila Sufina; Panggabean, Aman Sentosa; Kartika, Rudi (Jurusan Kimia FMIPA UNMUL, 2017)
The research about analytical performance optimization to the determination of fluorine’s concentration inside coal using visible spectrophotometry method has been done. The optimum result of the obtain for measurement, some parameters of measurements were validated. Parameters of validation used in this research are accuracy, precision, linearity, LOD, LOQ and robustness of the method. The results of research obtained, the accuracy was 99,34% described in percent of the recovery, obtained precision are 0,4309% described in percent of RSD with linearity equation was y = 10,79x + 16,77. The result of measurement is very good which described by the value of LOD 0,0638 ppm and LOQ 0,2127 ppm. The conclusion of results are the determination of fluorine's concentration inside coal using visible spectrophotometry method have good precision and accuracy which can be accounted.